EVALUATION OF ADVANCED STAGE TESTICULAR CANCER UNDERWENT CHEMOTHRAPY WITH BLEOMYCIN, ETOPOSIDE AND CISPLATIN IN ARIFIN ACHMAD REGIONAL GENERAL HOSPITAL IN 2009-2014 - Fellyana Putri; Zuhirman "; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Testicular cancer has become the only curable malignancy especially in advanced stage with chemotherapy. The aim of the study was to evaluate the complications, curability and recurrency of advanced stage testicular cancer underwent chemotherapy with bleomycin (B), etoposide (E) and cisplatin (P). All cases of advanced stage testicular cancer underwent chemotherapy with bleomycin, etoposide and cisplatin in Arifin Achmad Regional General Hospital of Riau Province were included in this study. There were 15 cases of advanced stage testicular cancer in this study in which 9 cases (60%) were advanced stage and 6 cases (40%) were the initial stage. In all advanced stage cases, 6 cases (66,7%) underwent chemotherapy, from these 6 cases, 5 cases (83,3%) underwent complete chemotherapy and 1 case (16,6%) underwent uncomplete chemotherapy (1 cycle). The most common short-term complication was nausea and vomiting (90,5%) followed by anxiety (85,7%), fatigue (80,9%), alopecia (42,85%), hyperthermia (9,52%), bleeding (4,7%) and thrombocytopenia (4,7%). Nephrotoxicity (42,8%) was the most common long-term complication of the chemotherapy followed by pulmotoxicity (9,5%) and neurotoxicity (4,76%). All cases (100 %) were curable after finishing 4 cycles of bleomycin, etoposide and cisplatin chemotherapy. The recurrency was 20%. Management of advanced testicular cancer with 4 cycles of bleomycin, etoposide and cisplatin chemotherapy proved low complication, high rate of curability and low recurrency.Keywords : testicular cancer, advanced stage, BEP, chemotherapy, recurrency.